Papel das vias de reconhecimento de ácidos nucléicos TLR3-TRIF e cGAS-STING e de seu produto IFN-tipo I na infecção por Neospora caninum - Miranda, Vanessa dos Santos (2020)
Neospora caninum is an obligatory intracellular parasite that belongs to the phylum Apicomplexa and is the causative agent of neosporosis, a disease of great importance in veterinary medicine to cause repeated abortions in cattle by the transplacental transmission of the parasite, generating great economic losses in beef and dairy sectors. The economic importance of neosporosis has led to several studies in the development of strategies for the prevention and treatment of this infection, including researchs related to innate immunity against this parasite. In this context, our work aimed to study the participation of innate pathways of nucleic acid recognition, TLR3-TRIF and cGAS-STING, as well as their common product IFN-type I in N. caninum infection. We observed that TLR3-/- and TRIF-/- mice have high parasite loads, increased tissue inflammation and reduced production of IL-12p40, TNF, IFN-γ and nitric oxide. In addition, we demonstrated that N. caninum RNA recruits TLR3 for the parasitophore vacuole and induces translocation of IRF3 to the cell nucleus, activating the production of Type I IFN. We also saw that TRIF gene expression is increased during N. caninum infection in macrophages, inducing, in turn, increased expression of IFN-α and IFN-β and in infected TRIF-/- macrophages there was a reduction in IL-12p40 production, which was completely reestablished with the replacement of recombinant IFN-α. Our next objective was to verify whether, like RNA, the DNA of N. caninum would have the same ability to activate and induce Type I IFN, in which case it would be recognized by the cGAS-STING pathway. Our results demonstrated that N. caninum DNA is capable of inducing the production of high concentrations of IFN-α and IFN-β. In addition, we observed that N. caninum tachyzoites induce cytosolic recruitment of cGAS and STING after cell invasion and this recruitment occurs due to the recognition of its DNA by these nucleic acid sensors. We confirmed in the Neospora study model, that the cGAS-STING pathway is essential for the production of IFN-α and IFN-β, since infection of STING-/- cells with tachyzoites or stimulus with their DNA generates dramatically reduced levels of these cytokines. We also observed that STING positively modulates the production of IL-12 and IL-10, which are important cytokines in the immune response against N. caninum, and that the control of parasite replication in infected macrophages is impaired in the absence of this molecule. Finally, we evaluated the importance of Type I IFN, a common product of the TLR3 and cGAS pathways, in the resistance of mice infected with the protozoan N. caninum. For this, we analyzed the morbidity and mortality rates in WT and IFNAR-/- animals infected with N. caninum tachyzoites monitored for 30 days after infection and it was observed that in the absence of Type I IFN, mice are more susceptible to infection. Then, we performed acute and chronic infections for analysis of parasitism and tissue inflammation, production of cytokines, nitric oxide and specific antibodies. We observed that the IFNAR-/- mice had a higher parasite load on the cells of the peritoneal lavage, lungs, liver and brain when compared to WT. In addition, the knockout animals showed a moderate degree of hepatic and brain tissue inflammation, with multiple inflammatory foci and, occasionally, the appearance of necrotic lesions, while the WT animals showed a mild degree of inflammation. Regarding the production of cytokines, we saw that in the absence of Type I IFN, the production of IL-12 and IFN-γ is compromised in the serum, peritoneal lavage and liver of infected animals and the production of nitric oxide also being reduced. To confirm these results, we performed cytokine dosage also in vitro, in culture supernatant of bone marrow-derived macrophages (BMDMs) from WT and IFNAR-/- mice, and we observed that during the N. caninum infection there is a significant reduction in production of IL-12 and IL-10 in knockout macrophages compared to WT. Finally, we evaluated the influence of Type I IFN on the production of anti-N. caninum antibodies and we observed that these cytokines have no direct influence on the humoral immune response development during the course of the infection. Together, our results showed that N. caninum RNA is recognized by the TLR3-TRIF pathway, which acts on the resistance of infected mice by controlling parasitism and tissue inflammation, important markers of the disease. In addition, N. caninum DNA is recognized by the cGAS-STING pathway and induces the production of IFN-type I, which acts together with the Th1-type immune response to control parasite replication and increase cell resistance to infection.